HUBUNGAN ANTARA MAJELIS TAKLIM DENGAN KELUARGA SAKINAH DI KAMPUNG REMPAK KECAMATAN SABAK AUH KABUPATEN SIAK - Kuramin, Siti; Marnelly, T. Romi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research aimed to determine the correlation between majelis taklim and sakinah family in Rempak village, Sabak Auh Sub-Regency, Siak Regency. This research was quantitative research that analyzed based on inferential statistic. The theory of the research was Functional theory which uses simple random sampling as the technique. from 147 population, 60 samples was taken by using Slovin formula. The samples as respondents was formed by using lottery technique. The results obtained in the field that the correlation between majelis taklim and sakinah family, based on qualification level of correlation, is on moderate level with 0,592 as the value of Pearson Correlation. Overall the participation of respondents in the majelis taklim, 50% of respondents included in very good category, 45% of the respondents in good category, and 5% of respondents in less good category. Meanwhile, the quality of sakinah family of respondents is 26,67% and categorized as very good, 70% of the respondents are in good category and 3.33% of respondents are in the less good category. Based on the significance value of Coefficient table obtained significance value that is equal to, 000 <0.05, so it can be concluded that the variable "Majelis Taklim (X) affects the variable Sakinah Family (Y)" which means that H0 is rejected and H1 is accepted. by regression test, obtained that coefficient of determination (Rsquare) is equal to 0.351 which means the effect of independent variables (majlis taklim) to the dependent variable (sakinah family) is 35.1%. While 64.9% is effected by other unexpected variables.Keywords: The Correlation, Majelis Taklim, Sakinah Family